Prenatal diagnosis of a silver-russell syndrome caused by 11p15 duplication and pedigree analysis - Hong, Shurong; Wei, Hua; Zhuang, Xueyi; Huang, Weirong; Zhang, Yu (Frontiers in Genetics, 2024)
IntroductionSilver-Russell syndrome (SRS) is an imprinting disorder characterized by intrauterine and postnatal growth retardation. The pathogenic alterations and phenotypes are heterogeneous.MethodsHere, we present a rare pedigree of duplications with different methylation patterns in 11p15.5, which caused SRS or a normal phenotype across three generations.ResultsDuplications of maternal IC2 (copy number of 3) with enhanced methylation (methylation index of 0.62) resulted in typical SRS.ConclusionThe result added to the complexity of the molecular genetics of SRS.